The Influence of Digital Competency on Teachers’ Functional Skills: Communication, Time Management, and Problem-Solving on Islamic teachers’ functional skills in southern, Pakistan - Muhammad Kashif Majeed; Tunku Badariah Binti Ahmad (Marasofi International Media and Publishing (MIMP), 2025)
The increasing integration of digital tools in education necessitates teachers’ proficiency in digital competency to enhance their functional skills, particularly in communication, time management, and problem-solving. This study investigates the influence of digital competency on the functional skills of Islamic Studies teachers in Southern Pakistan. Using a quantitative approach, data were collected from 450 secondary school teachers via structured questionnaires. Descriptive statistics and multiple linear regression analyses were conducted using SPSS to examine relationships among variables. Results revealed a significant positive correlation between digital competency and communication and time management skills, while the impact on problem-solving was present but less pronounced. Informal digital learning and AI tools were also found to moderate and strengthen these relationships. Teachers with higher digital proficiency demonstrated improved classroom and administrative performance. The study underscores the need for targeted professional development and adequate digital infrastructure to support teachers in under-resourced regions. It is recommended that institutions invest in training, peer mentoring, and access to technology to enhance teachers’ capacity in leveraging digital tools for functional effectiveness. These findings provide critical insights for policymakers and education stakeholders aiming to foster teacher readiness in digitally evolving educational environments.